ANALISIS TUMBUH KEMBANG ANAK DITINJAU DARI ASPEK PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI - Aip Saripudin (IAIN Syekh Nurjati Cirebon, 2019)
Abstract: The golden age of the humans is going on since a child was born until the age of eight years. In this case the growth and development of kids drove rapidly, so it needs an effective stimulation of parents and their environment. The growth is quantitative changes that happen to people in terms of the growing number and size of, the dimensions on a cellular level as well as organ which occurs on any individual. Temporary out growth qualitative which the process that refers to the improvement of social and psychological people and going on all his life human. In aspects of the development of early childhood, rough motor there will be growth and child development sustainable. Of course, hand in hand growth and development to the various aspects of an early age will walk in accordance with, phases of his age so parents need to have a comprehensive knowledge about various aspects in early childhood.Key Word: Growth and development, rough motor, early childhood Abstrak: Masa golden age pada manusia terjadi sejak anak dilahirkan hingga usia delapan tahun. Pada masa ini pertumbuhan dan pekembangan anak melaju pesat, sehingga perlu stimulasi yang efektif dari orang tua dan lingkungannya. Pertumbuhan merupakan perubahan yang bersifat kuantitatif yang terjadi pada manusia dalam hal bertambahnya jumlah dan ukuran, dimensi pada tingkat sel serta organ yang terjadi pada setiap individu. Sementara perkembangan yakni proses kualitatif yang mengacu pada penyempurnaan fungsi-fungsi sosial dan psikologis dalam diri seseorang dan berlangsung sepanjang hidupnya manusia. Dalam aspek perkembangan motorik kasar anak usia dini, maka akan terjadi pertumbuhan dan perkembangan anak secara berkesinambungan. Tentunya secara beriringan, pertumbuhan dan perkembangan berbagai aspek pada anak usia dini akan berjalan sesuai dengan tahapan usianya, sehingga orang tua perlu memiliki pengetahuan yang menyeluruh tentang berbagai aspek pada anak usia dini.Kata Kunci: Tumbuh kembang, motorik kasar dan anak usia dini